2016
DOI: 10.1146/annurev-fluid-122414-034345
|View full text |Cite
|
Sign up to set email alerts
|

Motion and Deformation of Elastic Capsules and Vesicles in Flow

Abstract: This article reviews the mechanical behavior of a capsule under the influence of viscous deforming forces due to a flowing fluid. It focuses on artificial capsules and vesicles with an internal liquid core enclosed by a very thin membrane with different constitutive laws. The recent modeling strategies are outlined together with their respective advantages and limitations. I then consider the motion and deformation of a single, initially spherical capsule freely suspended in a simple shear or plane hyperbolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
187
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(192 citation statements)
references
References 99 publications
3
187
0
Order By: Relevance
“…The thickness of the capsule wall is assumed to be infinitely small. A very thin hyperelastic membrane can be modelled as a zero-thickness elastic surface, with different possible constitutive laws (Barthès-Biesel 2016). Among those, the Skalak's (SK) law (Skalak et al 1973), which was originally proposed to describe the membrane of a RBC, assumes a strain energy function of the form…”
Section: Problem Descriptionmentioning
confidence: 99%
“…The thickness of the capsule wall is assumed to be infinitely small. A very thin hyperelastic membrane can be modelled as a zero-thickness elastic surface, with different possible constitutive laws (Barthès-Biesel 2016). Among those, the Skalak's (SK) law (Skalak et al 1973), which was originally proposed to describe the membrane of a RBC, assumes a strain energy function of the form…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Since both the particle and the suspending medium are inertialess, no initial conditions on the velocities are required, whereas an initial condition is needed on the extra-stress tensor. We assume that the particle (and the matrix, in case it is viscoelastic) is initially stress-free, which means: τ| t=0 = 0 (14) The above listed equations are made dimensionless by choosing the channel diameter D c as the characteristic length, the unperturbed average velocity of the fluid u av = 4 Q/π D 2 c as the characteristic velocity, the ratio between the characteristic length and the characteristic velocity D c / u av as the characteristic time, μu av / D c (or μ 0 u av /D c ) as the characteristic stress in the matrix, and the shear modulus of the elastic material G p as the characteristic stress in the particle. All the variables appearing in the following Sections are made dimensionless through such characteristic quantities.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Very recently, Villone et al [12] studied through direct numerical simulations the deformation and cross-streamline migration of an initially spherical elastic particle in confined shear flow of both Newtonian and viscoelastic fluids. It was demonstrated that, at variance with rigid particles, elastic particles migrate orthogonally to the flow direction even in inertialess flows of Newtonian fluids; notice that such a migration was already known to occur also for other deformable particles, like Red Blood Cells (see, for example, the review by Geislinger and Franke [13] and the references therein), and vesicles or capsules (see the review by Barthès-Biesel [14] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a capsule in shear flow is a fundamental process that is related to erythrocytes (or red blood cells), leukocytes (or white blood cells), and platelets in blood flow [16]. Deformation is essential for red blood cells to perform their physiological functions in the circulation of capillary blood vessels and thus affects the rheology of the blood [68]. The deformations of white blood cells and red blood cells can, respectively, affect the immune response and the oxygen load release [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic microcapsules with polymerized interfaces are designed for drug delivery, cosmetic production, and other technical usages [11, 12]. Therefore, great effort has been made to study this problem (e.g., [1, 4, 6, 8, 10, 1214]).…”
Section: Introductionmentioning
confidence: 99%